1996
DOI: 10.1111/j.1432-1033.1996.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Two Different Mannose‐Binding Lectins from Tulip Bulbs

Abstract: Two lectins were isolated from the bulbs of Tulipa cv. Apeldoom and their corresponding cDNA clones analyzed. The first, called TxLMII (second mannose-binding Tulipa hybrid lectin), is a novel mannose-binding tulip lectin. Based on its molecular structure, carbohydrate-binding specificity and amino acid sequence, TxLMII belongs to the superfamily of mannose-binding monocot lectins which are also found in representatives of the plant families Amaryllidaceae, Alliaceae, Orchidaceae and Araceae. Molecular cloning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 41 publications
0
24
0
3
Order By: Relevance
“…Detailed studies of the different lectins present in a number of monocot species such as garlic (Allium sativum), ramsons (Allium ursinum) and tulip (Tulipa sp. ), have demonstrated that they are all closely related at the molecular level [19][20][21].…”
Section: Discussionmentioning
confidence: 98%
“…Detailed studies of the different lectins present in a number of monocot species such as garlic (Allium sativum), ramsons (Allium ursinum) and tulip (Tulipa sp. ), have demonstrated that they are all closely related at the molecular level [19][20][21].…”
Section: Discussionmentioning
confidence: 98%
“…A combination of mannose and GalNAc also failed to prevent the agglutination of rabbit erythrocytes by SCAfet. Therefore the apparent complex specificity of SCAfet cannot be ascribed to the simultaneous occurrence of both mannose-and GalNAc-binding domains as was demonstrated for a related fetuin-binding lectin from tulip bulbs [11]. Assays with some animal glycoproteins revealed that the agglutination activity of SCAfet can be inhibited by thyroglobulin, asialofetuin, fetuin and ovomucoid, the concentrations required for 50 % inhibition being 60, 16, 250 and 125 µg\ml respectively.…”
Section: Carbohydrate-binding Specificity and Biological Activities Omentioning
confidence: 95%
“…In a later experiment cDNA clones encoding the S. campanulata lectins were used as probes. Hybridization was performed overnight as reported previously [11]. Colonies that produced positive signals were selected and rescreened at low density under the same conditions.…”
Section: Rna Isolation and Construction And Screening Of Cdna Librarymentioning
confidence: 99%
See 2 more Smart Citations